Bone Marrow Aspirate Concentrate (BMAC) for Knee Osteoarthritis: A Narrative Review of Clinical Efficacy and Future Directions - Dojoon Park; Hae-Seok Koh; Youn-Ho Choi; Ilkyu Park (Medicina)
Bone marrow aspirate concentrate (BMAC) is an autologous regenerative therapy enriched with mesenchymal stem cells (MSCs) and bioactive growth factors, offering potential disease-modifying effects in knee osteoarthritis (OA). Compared to conventional intra-articular treatments, including hyaluronic acid (HA), platelet-rich plasma (PRP), and corticosteroids, BMAC promotes cartilage regeneration, modulates inflammation, and enhances subchondral bone remodeling. Clinical evidence suggests that BMAC provides short- to mid-term symptomatic relief and functional improvement, with some studies indicating a potential to delay total knee arthroplasty (TKA). However, findings remain inconsistent, and long-term efficacy compared to PRP or autologous conditioned serum (ACS) is yet to be firmly established. Variability in BMAC preparation methods, injection protocols (single vs. repeated administration, intra-articular vs. subchondral delivery), and patient selection criteria complicates its clinical application, highlighting the need for standardized guidelines. Additionally, economic feasibility and cost-effectiveness concerns limit its widespread adoption. This review synthesizes current clinical evidence, evaluates optimal administration strategies, and explores future directions for improving treatment standardization and patient-specific therapy. Future research should prioritize well-designed, multicenter randomized controlled trials (RCTs) with long-term follow-up to confirm the sustained efficacy and therapeutic potential of BMAC in OA management.